Pengembangan Soal Matematika Model TIMSS Sebagai Instrumen Penilaian Matematika Siswa SMP - Septiati, Ety (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2025)
This study aims to develop TIMSS model mathematics questions as an assessment instrument. The method used is the 4-D model development method (Define, Design, Develop, Disseminate). The research subjects were two eighth-grade junior high school students for the pilot test and two experts to assess the validity of the questions developed. The subjects were selected using purposive sampling based on their involvement, experience, and availability. The instruments used were the TIMSS-model mathematics question package, as well as student and teacher response sheets. Data were analyzed qualitatively. The results of the question item development showed that the three questions developed through adaptation from TIMSS questions were deemed valid. The expert validation and revision process significantly improved the language, instructions, and visual quality. Based on the pilot test results, it was found that students still struggled with solving reasoning-level questions.